What Factors Affect the Consumptive Behavior of Millennial Generation Shopee Latter Users in DKI Jakarta - Putri, Nabila Isabelina; Nasution, Annanta Hagabean (Universitas Fajar, 2024)
This study aims to identify the factors influencing the consumptive behavior of Shopee PayLater users among the millennial generation in DKI Jakarta. The research falls under the category of quantitative research, with a sample size of 200 respondents who are Shopee PayLater users. Data collection was conducted using a questionnaire, while the sample was selected using purposive sampling techniques. Data analysis was performed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method. The results of the study reveal that financial literacy and peer environment have a positive and significant effect on consumptive behavior. In contrast, lifestyle does not influence consumptive behavior. Furthermore, purchasing decisions also have a positive and significant effect on consumptive behavior. Financial literacy, lifestyle, and peer environment all positively and significantly affect purchasing decisions. Additionally, purchasing decisions mediate the relationship between financial literacy, lifestyle, and peer environment on consumptive behavior.